TINJAUAN HUKUM HAK ROYALTI LAGU DALAM PEMBAGIAN HARTA GONO GINI PASCA PERCERAIAN Kajian Putusan 1662/Pdt.G/2023/PAJB - Andriani, Sesi (Jurnal Jejak Hukum Indonesia (JHI), 2024)
This scientific work discusses the legal provisions regarding royalty rights as a division of mutually beneficial assets between divorced married couples. The author's aim in choosing this title is to reveal the legal aspects and juridical provisions regarding the distribution of mutually beneficial assets for divorced husband and wife couples. This research uses a normative legal research method which uses literature review as an effort to find the necessary data. Review legal documents that focus on Legislation. Islam recognizes the existence of tangible assets and intangible assets. HKI are classified as intangible assets, namely industrial property rights relating to inventions in the industrial sector and copyrights relating to art, literature and science. HKI is a movable object, it can be transferred either by gift, inheritance or in other ways according to the agreement or based on applicable laws and regulations (Article 3 of Law No. 19 of 2002).